Prevalence and Influencing Factors of Motoric Cognitive Risk Syndrome Among Older Adults in Long-Term Care Facilities - Xinxin He; Yangyang Jiang; Langli Gao; Juan Lv; Ying Li (Healthcare, 2026)
Background/Objectives: To investigate the prevalence of the Motoric Cognitive Risk (MCR) Syndrome among older adults in long-term care facilities and its associated risk factors. Methods: From January to December 2024, older adults were recruited from five long-term care facilities in Southwest China via convenience sampling. All participants underwent a series of standardized assessments, including a self-designed demographic questionnaire, the 15-item Geriatric Depression Scale (GDS-15), the Timed Up and Go (TUG) test, the Fried frailty phenotype scale, sarcopenia assessment based on the SARC-F sarcopenia screening scale, the Basic Activities of Daily Living (BADL) scale, the Lawton Instrumental Activities of Daily Living (IADL, Lawton) scale, and the Mini-Mental State Examination (MMSE). The 4 m walk test was performed to measure participants’ gait speed. This cross-sectional study aimed to explore the prevalence of MCR syndrome and its associated influencing factors among institutionalized older adults. Results: The overall MCR prevalence was 8.6%. Univariate tests detected intergroup differences in BMI, depressive symptoms, hearing loss, multimorbidity, mobility impairment, frailty and several chronic diseases (all p < 0.05). Multivariate logistic regression analysis further demonstrated that, after adjustment for confounders, higher depressive symptom scores (OR = 1.169, 95% CI: 1.079–1.265, p < 0.001), mild mobility impairment (OR = 4.725, 95% CI: 1.340–16.663, p = 0.016), moderate mobility impairment (OR = 3.921, 95% CI: 1.146–13.420, p = 0.029), and more than three chronic comorbidities were independent risk factors for MCR among institutional older adults residing in long-term care facilities (OR = 2.789, 95% CI: 1.465–5.309, p = 0.002). Conclusions: Depressive symptoms, mild-to-moderate mobility impairment and multimorbidity were independent correlates of MCR among institutional older adults. Distinct risk-factor patterns existed for SG and SCCs, highlighting the separable nature of motor and subjective-cognitive dimensions. Integrated screening for emotional, physical and chronic disease risk and personalized activity interventions are warranted for long-term care residents.